Pengaruh Mekanisme Good Corporate Governance Terhadap Agresivitas Pajak Di Bumn Yang Terdaftar Pada BEI Periode 2016-2020 - Shelvi Shelvi; Irvan Liunardi Senjaya; Theresia Gunawan; Dian Sadeli (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The aim of this study was to assess and analyze the level of tax aggressiveness that implemented Good Corporate Governance (GCG) mechanism by state-owned companies in Indonesia. Tax aggressiveness was measured by Effective Tax Rate (ETR) and GCG mechanism was measured by independent commissioners, audit committee, board of directors, and institutional ownership. The population that being used was state-owned companies that listed in Indonesia Stock Exchange (IDX) that had shown financial statement from 2016-2020. Data process using regression analysis were used to test interaction between dependent and independent variables. Result showed that GCG mechanism had influenced simultaneously to tax aggressiveness. If they were partially tested, only audit committee and board of director proxies that were influenced to tax aggressiveness because they had been considered to have carried out its function properly so that it was able to suppress actions that are not in accordance with GCG principles. Keywords: Good Corporate Governance, Tax Aggressiveness, Effective Tax Rate